Awareness of implants as an option in dental treatment. A study held in college of dentistry, Tikrit University - Arab, LumaNasrat (International Journal of Psychosocial Rehabilitation, 2020)
Loss of teeth is a condition that affects the patient functionally, esthetically and psychologically. The use of dental implants in complete and partial edentulismis an effective choice for prosthetic replacement. However, patient’s awareness concerning this choice is still very little, and there is no survey held in Tikrit University to estimate the degree of Knowledge regarding this subject.To estimate the degree of awareness of the need for implants in dental treatment among the staff and students of Tikrit university. A questionnaire has been prepared and given randomly to 100 teachers and students in Tikrit university and informationgatheredfrom it. Then using IBM SPSS 23 statistical program to manage the data.A sample of 100 patients were randomly selected for this survey.Most participants were aware of using implant as an option in teeth replacement 78.3%.According to the results it was found that the main source of participants knowledge of implants was from friends and relatives as was shown in the percentage of answers(45.4 %). The highest percentage (72 %) answered that an implant lasts less than 5 years,the greatest percentage (46%) answered that the fear of surgery is the main reason preventing them from having an implant. • There is a good awareness among participants of the use of • Most of the information about implants came from friends and relatives. There is also a great impact of media on this subject. So there should be more efforts from dentists to educate people. • Educational programs must be made to explain the materials, surgical operation, benefits and risks of implants as a choice in teeth replacement.